Postharvest physiology of fruits and vegetables and their management technology: A review - Dr. Md. Iqbal Hossain; Dr. Jannatul Ferdousi; Dr. Satya Ranjan Saha; Dr. Md. Mahfuzur Rob; Tahmina Afroz; Dr. Shila Pramanik; Dr. Md. Rabiul Islam; Dwipak Deb Nath (Journal of Animal and Plant Sciences, 2024)
This review basically provides the knowledge regarding postharvest physiology, allied factors and managements of harvested horticultural produce. Commodities with higher respiration and ethylene production tend to have shorter shelf life with low quality than those with lower respiration and ethylene production. Transpiration and respiration processes of harvested fruits and vegetables results in weight loss, softening and shriveling, loss of peel glossiness etc. Fruit and vegetable storage life is negatively impacted by ethylene production. Fungi and bacteria are the biggest offenders among almost all postharvest disorders of fruits and vegetables. One of the largest significant factors impacting the postharvest life of fruits and vegetables is temperature because it has intense influence on the rate of physiological responses such as, respiration, transpiration, ethylene production and diseases development. The rate of respiration and the generation of ethylene are both regulated by high temperatures. On the other hand, high temperature with high relative humidity favors the diseases development but low temperature (5oC) and high relative humidity (RH 96%) results in low transpiration. Control or modified atmosphere storage (O2 below 5%, CO2 above 3%), vacuum pack, chemical treatments and edible coating are the effective ways for controlling respiration, ethylene production, transpiration and diseases development but it is mainly dependent on types of fruits and vegetables.
Keywords: Postharvest Physiology; Storage life; Transpiration; Respiration; Ethylene; Temperature; Controlled